Anatomical Profile of Vertebrobasilar System Based on Angiographic Studies - Gilbert Tangkudung; Finny Warouw; Kennytha Yoesdyanto; Vinson Hartoyo (Journal of Neurointervention and Stroke, 2025)
Highlight: Anatomical variations in blood vessels can significantly affect circulatory hemodynamics These variants also pose a risk of developing intracranial pathologies such as aneurysms Early detection can help prevent further complications ABSTRACT Introduction: Variations of cerebral vasculature in vertebrobasilar system (VBS) occur during embryogenesis and may contribute to cerebrovascular events. These anatomical variants occur in approximately 7% of cases with a 91% prevalence noted in the symmetrical caudal fusion variant. Cerebral angiography remains the most sensitive method for diagnosing these anomalies. Objective: This study aimed to identify angiographic variations in the VBS.  Method: This descriptive observational study used a cross-sectional approach, analyzing secondary data from stroke patients who underwent angiographic procedures between December 2017 and August 2020 at Prof. dr. R. D. Kandou Hospital, Manado. The sample size included the total population of stroke patients who met the inclusion criteria. Data were processed using SPSS version 32. Result:  A total of 277 samples were analyzed. The most commonly observed variations were symmetric cranial fusion (81.50%) and asymmetric caudal fusion (15.42%). One case of symmetric caudal fusion had a basilar tip aneurysm. While most patients exhibited normal anatomy, variants of the posterior cerebral artery (PCA) were also observed, including absence (6.17%) and hypoplasia (7.48%). The superior cerebellar artery (SCA) was absent in 1.76% of cases. Absence of the anterior inferior cerebellar artery (AICA) and posterior inferior cerebellar artery (PICA) was observed in 13.56% of cases; however, these were compensated by complex vascular formations involving collateral sources (21.58%). Conclusion: This study concludes that anatomical variations in cerebral vasculature, including perforators and anastomoses, can be effectively observed through angiographic studies.Careful patient selection is essential to rule out secondary causes of hemifacial spasm and to identify underlying neurovascular contacts.